Placement Distance of Exit Advance Guide Sign on an Eight-Lane Expressway Considering Lane Changing Behaviour in China - Su, Xiaozhi; Ma, Yanfeng; Li, Rui; Sun, Xujiao; Han, Yanwen (Promet - Traffic&Transportation, 2022)
The reasonable placement of the advance guide signs (AGSs) is important in improving driving efficiency and safety when exiting an expressway. By analysing the lane-changing process when approaching an exit on new two-way eight-lane expressways, we modified the tradi-tional AGS model lane-change distance formula. To this end, a field experiment was designed to explore the lane-change traversal time at the free flow condition (LOS 1). Considering the limitations of the experimental equip-ment, lane change distance at the worst levels of service was explored using VISSIM simulation. The results show that the eight-lane changing distance based on modified theoretical calculations, revealed a minor difference with VISSIM simulation in free flow condition. Further-more, placement distance at the worst levels of service are discussed. Then placement distance of all-level AGSs is recommended to be 3 km, 2 km, 1.2 km, and 0.8 km, considering the driver’s short-term memory attenuation calculation formula. Determining the two-way eight-lane AGS placement distance from the perspective of LOS can provide a basis on which to supplement the existing stan-dards and references for the AGS placement distance af-ter the expressway expansion in China.